Fecal Implants From AppNL–G–F and AppNL–G–F/E4 Donor Mice Sufficient to Induce Behavioral Phenotypes in Germ-Free Mice - Kundu, Payel; Stagaman, Keaton; Kasschau, Kristin; Holden, Sarah; Shulzhenko, Natalia; Sharpton, Thomas J.; Raber, Jacob (Frontiers in Behavioral Neuroscience, 2022)
The gut microbiome and the gut brain axis are potential determinants of Alzheimer’s disease (AD) etiology or severity and gut microbiota might coordinate with the gut-brain axis to regulate behavioral phenotypes in AD mouse models. Using 6-month-old human amyloid precursor protein (hAPP) knock-in (KI) mice, which contain the Swedish and Iberian mutations (APP NL-F (AppNL-F)) or the Arctic mutation included as third mutation (APP NL-G-F (AppNL-G-F)), behavioral and cognitive performance is associated with the gut microbiome and APP genotype modulates this association. In this study, we determined the feasibility of behavioral testing of mice in a biosafety cabinet and whether stool from 6-month-old AppNL-G-F mice or AppNL-G-F crossed with human apoE4 targeted replacement mice is sufficient to induce behavioral phenotypes in 4-5 month-old germ-free C57BL/6J mice 4 weeks following inoculation. We also compared the behavioral phenotypes of the recipient mice with that of the donor mice. Finally, we assessed cortical A levels and analyzed the gut microbiome in the recipient mice. These results show that it is feasible to behaviorally test germ-free mice inside a biosafety cabinet. However, the host genotype was critical in modulating the pattern of induced behavioral phenotypes as compared to those seen in the genotype- and sex-match donor mice. Male mice that received stool from AppNL-G-F and AppNL-G-F/E4 donor genotypes tended to have lower body weight as compared to wild type, an effect not observed among donor mice. Additionally, AppNL-G-F/E4 recipient males, but not females, showed impaired object recognition. Insoluble A40 levels were detected in AppNL-G-F and AppNL-G-F/E4 recipient mice. Recipients of AppNL-G-F , but not AppNL-G-F/E4, donor mice carried cortical insoluble A40 levels that positively correlated with activity levels on the first and second day of open field testing. For recipient mice, the interaction between donor genotype and several behavioral scores predicted gut microbiome alpha-diversity. Similarly, two behavioral performance scores predicted microbiome composition in recipient mice, but this association was dependent on the donor genotype. These data suggest that genotypes of the donor and recipient might need to be considered for developing novel therapeutic strategies targeting the gut microbiome in AD and other neurodegenerative disorders.